Cross-sectional study of proteomic differences between moderate and severe psoriasis - Lingling Wu; Chen Cen; Bibo Xie; Lihua Hu; Jia Huang; Ningning Shen; Qiang Dong (Scientific Reports)
Abstract Although an ongoing understanding of psoriasis vulgaris (PV) pathogenesis, little is known about the proteomic differences between moderate and severe psoriasis. In this cross-sectional study, we evaluated the proteomic differences between moderate and severe psoriasis using data-independent acquisition mass spectrometry (DIA-MS). 173 differentially expressed proteins (DEPs) were significantly differentially expressed between the two groups. Among them, 85 proteins were upregulated, while 88 were downregulated (FC ≥ ± 1.5, P < 0.05). Eighteen DEPs were mainly enriched in the IL − 17 signalling pathway, Neutrophil extracellular trap formation, Neutrophil degranulation and NF − kappa B signalling pathway, which were associated with psoriasis pathogenesis. Ingenuity pathway Analysis (IPA) identified TNF and TDP53 as the top upstream up-regulators, while Lipopolysaccharide and YAP1 were the top potential down-regulators. The main active pathways were antimicrobial peptides and PTEN signalling, while the inhibitory pathways were the neutrophil extracellular trap pathway, neutrophil degranulation, and IL-8 signalling. 4D-parallel reaction monitoring (4D-PRM) suggested that KRT6A were downregulated in severe psoriasis. Our data identify Eighteen DEPs as biomarkers of disease severity, and are associated with IL − 17 signalling pathway, Neutrophil extracellular trap formation, NF − kappa B signalling pathway, and defence response to the bacterium. Targeting these molecules and measures to manage infection may improve psoriasis’s severity and therapeutic efficacy.